Strategi Evaluasi, Pelaporan, dan Tindak Lanjut untuk Meningkatkan Efektivitas Layanan BK di Sekolah - Christiana, Elisabeth; Hati, Adinda Mutiara; Rakhmanita, Aulia; Pratama, Gadis Putri Amelia; Asmarani, Eka Meylana (Lembaga Yasin AlSys, 2025)
In this Study, the researcher is interested in examining the evaluation, reporting, and follow-up strategies to improve the effectiveness of guidance and counseling services in schools, both at the elementary/Islamic elementary school, junior high school/Islamic junior high school, and senior high school/vocational high school/Islamic senior high school levels. This study aims to deepen the understanding of evaluation, reporting, and follow-up strategies to improve the effectiveness of guidance and counseling services in schools. In their research, the reserchers used a qualitative approach through literature studies. Literature studies are the objects studied in this study, namely evaluation, reportiing, and follow-up strategies in guidance and counseling services in schools. The result of this study can be said that evaluation, reporting, and follow-up in guidance and counseling services are important components in ensuring the success of guidance and counseling services in school.